Examination of the sectoral overlap of COVID-19 and Brexit shocks - Luke Daly; Martina Lawless (The Economic and Social Research Institute (ESRI), 2020)
Ireland is currently dealing with a severe public health crisis from Covid-19, which has substantially reduced social and economic activity. Prior to the onset of the pandemic, the most imminent risk to the strong performance of the Irish economy seemed likely to come from a hard Brexit. This paper looks at sectoral exposure to both the Covid-19 and Brexit shocks to assess if there is a risk that the impact of a hard Brexit on an economy weakened by dealing with Covid-19 could make the previously estimated effects of Brexit worse. Using a range of data sources, we assign an exposure rank to 57 sectors of the economy for each shock, from most severely affected sectors to those that are effectively unaffected. Overall, we find that there is limited overlap in the sectors exposed to the different shocks. We further examine the flow of goods and services between sectors affected by the two shocks to establish the extent of potential supply chain transmission of the shocks. Our main finding is that the sectors exposed to each shock are not particularly closely connected to those affected by the other shock. These results suggest that adding the Brexit shock to that of Covid-19 brings a wider range of sectors exposed to risk but that the impacts are not magnified by interaction effects.
Keywords: 330; Coronavirus; Brexit; Schock; Branche; Irland